Analisis Hubungan Waktu Tunggu Pelayanan Resep Obat Racikan dan Non-Racikan dengan Kepuasan Pasien di Puskesmas Jambu Kulon - Apriliya Refiani Astuti; Murwati Murwati; Nur Atikah (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2023)
One of the causes of patients at the health centre feeling uncomfortable with the drug administration process is the problem of waiting time. Patient satisfaction is strongly influenced by waiting time indicators for health centre prescription services. Patient satisfaction will increase if the service time is faster, especially the time spent waiting for the drug. This study aims to determine the average waiting time for concocted and non-concocted prescription services, patient satisfaction levels, and the relationship between waiting time for concocted and non-concocted prescription services and patient satisfaction at the Jambu Kulon Health Centre, Klaten District. This research is a quantitative correlation with a cross sectional approach. The sampling technique was accidental sampling with a sample of 60 respondents. Collecting data and information on respondents using a valid questionnaire with a minimum value range of 0.422 to a maximum of 0.751 and a Cronbach’s Alpha value of 0.926. The results of the significant value obtained for concoction recipes p = 0.142 and non-cooking p = 0.702, while the correlation value of the Spearman test (r) for prescription drug -0.274 and nonprescription drug -0.073 indicates that the direction of the correlation is negative or the direction of the relationship is opposite, indicating that there is an inverse of proportionality between the two variables. The conclusion is that patient satisfaction and waiting time for prescription services are statistically not significantly correlated (p>0.05).